Trevor Lucius: capstone - Lucius, Trevor, artist (Colorado State University. Libraries, 2017)
The artist's statement: From a very young age I've felt compelled to create. This mainly came in the form of drawing on printer paper and in the margins and backs of my notebooks throughout grade school. In middle school I would depict classmates and friends of mine as cartoon characters at their request or just because I wanted to draw them. In my early twenties I began using computer programs as a new set of tools for creating artwork for local bands. It was around this time that I really became aware of graphic design as a legitimate career path and I felt as if it was the perfect marriage between the creation and promotion process that was so appealing to me years before. This fascination continued through self-published magazines, music projects, and eventually led me to pursue an education in graphic design. Though creating art has always been something I've drawn personal enjoyment from there is a persistent excitement for me in presenting and sharing my work with others. Creating in solitude has never fully satiated my passion of making, I always sought to entertain and amuse with my final pieces. I find inspiration in the 'do it yourself' ethics and the visual aesthetic of punk rock, vibrant skateboard art of the 90s, bold ink line work of comics, gritty guerrilla street art, and old Soviet propaganda posters. I use familiar iconography to draw on established connections. I prefer to keep my work free of overly technical rendering and vague messages, instead favoring simplicity and humor. I want to draw attention to my pieces in a way that a good billboard would momentarily draw a motorist's attention from the road and I want that message to be clear and concise. These messages are often social or political in nature though I aim to inject a bit of humor as to avoid unnecessary vulgarity and heavy-handedness. I create these scenes and images as a catharsis of my own internal dialogue and to soften cynical thoughts as a way to relate to and make sense of the human condition. I feel that this medium has the ability to communicate on an immediate, visceral way that polemics or a diatribe cannot. This is an exciting and also challenging problem to overcome for me and rewarding when I can discover a way of how to effectively make this happen. The way I get to my final piece is through a lot of preliminary brainstorming and sketching. I usually have a basic idea of a figure or image and then work to uncover it and go through many revisions before satisfied. Though it is tempting to jump on the computer and get to work right away on an idea the most successful ones spend a good majority of their time jotted down in notebooks and drawing pads. Outside of the computer and the popular Adobe software I use to manipulate images, my tools tend towards the more rudimentary: Pencils, pens, markers, and paper.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design